DEVELOPMENT OF IoT SYSTEMS FOR FIRE DETECTION TOOLS USING ESP 8266 AND TELEGRAM NOTIFICATIONS - Kurnia, Deni; Setiawan, Rudi; Janizal (LPPM Politeknik Enjinering Indorama, 2023)
This research describes the process of making and developing a fire detection system using IoTtechnology. The background for making this tool is because the existing tool at the research site, namely at the Captive Power Plant of PT Indorama, is still a conventional device with an ordinary smoke sensor system and notifications only via a buzzer. This system combines telegram notification mode. Using three sensors namely temperature sensor, smoke sensor and fire sensor is a very effective combination as an early warning system. The test results show that the system provides notification via telegram when there is a significant increase in temperature above 31oC. The smoke sensor is tested with three smoke conditions, namely thin, medium and thick with a value of 704-803 ppm. The sensor response is less than 2 seconds, notification instructions to telegrams are sent directly without any delay. In the fire sensor test, six test conditions were carried out with variations in distance ranging from 10-100 cm, the sensor response was under 2 seconds, immediately activated the buzzer and a telegram notification was sent. The results of this study contribute to the hope that with the three sensor combinations the security layer will be more optimal and in real terms it can be used in industrial buildings which are prone to fire.